Strategi Pengembangan Usaha Kafe “Inspirasi Kopi” Dengan Metode Business Model Canvas Dan Ten Types Of Innovation - Muhammad Razzaq Yogie Setiawan; Aries Kurniawan; Vembri Aulia Rahmi; Hadi Ismanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Muhammadiyah organization and also their business entity have a lot of branch in various region. In Kabupaten Gresik there are Economy and Entrepreneur Council PCM GKB and many business entity. One of the business entity is Inspirasi Kopi Cafe, that was focusing on food and beverages. This business entity relatively new so it needs more strategic and new innovation for the future progress. Business Model Canvas and Ten Types of Innovation is the most perfect business model to be used for the developmen of Inspirasi Kopi Cafe. In this research use qualitative approach, that was producing descriptive data from deep interview that was held. The data research collected from four diffent source person. From the result of this research that was developed using Ten Types of Innovation is profit model innovation, Innovation of Serve, Innovation that was involving consument and Innovation product system. Reseracher decide to rearrange the Business Model Canvas that was adopted from the old Business Model Canvas with a research using interview and obeservation method, so that it formed the remodelling business model canvas that can help develop the business entity of Inspirasi Kopi Cafe.